Comparison of Precision for Manual versus Robotic-Assisted Total Hip Arthroplasty Performed by Fellows - Smith, Ryan; Borukhov, Ilya; Hampp, Emily; Thompson, Matt; Byrd, Zackary O.; Sodhi, Nipun; Mont, Michael A.; Scholl, Laura (The Journal of Hip Surgery, 2020)
Although various studies have shown that robotic-assisted total hip arthroplasty (RATHA) is associated with improved component positioning to plan and reduced intraoperative complications, there is still a learning curve for implementation even for experienced surgeons. This study assessed this learning curve for fellows during their training year, by comparing the accuracy and precision of acetabular component positioning, leg length, component offset, and center of rotation between manual THA (MTHA) and RATHA. Six fresh-frozen lower extremity specimens were utilized for surgical procedures performed by two adult reconstruction fellows who were halfway through their training year. The specimens were randomized to undergo one side with manual instrumentation and the contralateral side with RATHA. The final intraoperative surgical plan for rotation, cup orientation, leg length, and offset values were recorded and compared with the actual values measured by computed tomography (CT) scan. Using pre- and postoperative CT scans, the RATHA group was then compared with the MTHA group for accuracy and precision to plan. To assess differences in standard deviations of each measurement, 2-variances testing was performed using α = 0.05. To assess differences in central tendencies of each measurement for each group, Mann–Whitney U tests were performed using α = 0.05. RATHA exhibited significantly (p < 0.05) greater accuracy and precision to plan compared with MTHA in shell version (2.3 ± 1.2° vs. 7.8 ± 4.6°), shell inclination (2.1 ± 1.2° vs. 7.2 ± 3.2), and leg length discrepancy (0.8 ± 0.8 mm vs. 6.4 ± 3.7 mm). Center of head rotation was reported for each anatomical plane. There was no statistical difference in distance from original center of head rotation when considering the superoinferior, mediolateral, and anteroposterior planes as well as when combined as a total deviation in all three planes. The use of CT-guided preoperative planning and intraoperative robotic technology can help surgeons achieve desired implant placement. Results from this study indicate that with limited RATHA experience, surgeons in fellowship training were able to place THA components more accurately and precisely to plan for several important parameters compared with MTHA, namely shell inclination, shell anteversion, and leg length discrepancy.
Keywords: robotic total hip arthroplasty; training; accuracy; precision